A cross-sectional study examining perceptions of discriminatory behaviors experienced and witnessed by veterinary students undertaking clinical extra-mural studies - Summers, Olivia S.; Medcalf, Rebecca; Hubbard, Katherine A.; McCarroll, Charlotte S. (Frontiers in Veterinary Science, 2023)
Introduction Recent research showed that 29% of respondents in a survey of veterinary professionals reported experiencing self-described discrimination in their workplaces. Senior colleagues and clients were those responsible for discriminatory behaviours. As part of their training, veterinary students are expected to undertake extra-mural study (EMS) within these same workplaces and are likely to be vulnerable to discrimination from senior colleagues and clients. This study’s objectives were to identify and characterise the pattern of perceived discriminatory behaviours (i.e. belief of being treated unfairly) that veterinary students encounter while seeing practice and explore students’ attitudes towards discrimination. Methods Students at British and Irish veterinary schools that undertook some clinical EMS completed a survey of closed and open questions as part of a cross-sectional study. Demographic data and experiences of discrimination with details of incidents and reporting were collected, alongside respondent attitudes. Quantitative data were analysed using Pearson’s chi-squared analysis to analyse respondents’ characteristics and their experiences of discriminatory behaviours and subsequent reporting. Qualitative content analysis was used for open question data. Results Of 403 respondents, 36.0% had perceived behaviour they believed was discriminatory. The most frequent form of discrimination was based on gender (38.0%), followed by ethnicity (15.7%). There were significant associations between respondents’ experience of discriminatory behaviours and the following characteristics: age (p=0.0096), disability (p<0.00001), race/ethnicity (p<0.0001), gender/sex (p=0.018) and LGBTQ+ status (p=0.001). Supervising veterinarians were the most commonly reported perpetrators of discriminatory behaviours (39.3%) compared with clients (36.4%). Only 13.9% of respondents who experienced discrimination reported the event(s). Respondents with a disability were the least likely to agree with the statement that professional bodies are doing enough to tackle discrimination (p<0.0001). Most respondents agreed that sexism is still an issue (74.4%), but men were more likely to disagree (p=0.004). Most respondents felt that ethnic diversity needed to be increased (96.3%). Discussion Discriminatory behaviour is a problem for students seeing practice, especially those with one or more protected characteristics (as defined by the UK Equality Act 2010). Improved education would need to include perspectives from minority groups to help remove discriminatory behaviour from veterinary practice.